Ecotourism and Conservation in the Americas - Stronza, Amanda (CABI, 2014)
Among today’s contending conservation and development strategies, ecotourism is one of the most popular. It seeks to curb the often deleterious effects of large-scale, conventional tourism on local communities and ecosystems. But more than that, it holds the promise of overcoming a number of today’s biggest environmental and social challenges. Ideally, ecotourism can help conserve biological and cultural diversity, alleviate rural poverty, strengthen ties between parks and neighbouring peoples, increase public awareness of environmental concerns, and manifest a new ‘triple bottom line’ for business that includes profit, social benefits and environmental conservation. For these reasons, interest in ecotourism has never been greater. According to the World Tourism Organization, ecotourism is now the fastest growing segment of an already mammoth tourism industry. By some estimates, ecotourism generates as much as US$300 billion in revenues annually. International development and lending agencies channel millions of dollars into projects that include ecotourism. Major conservation organizations sponsor ecotourism projects in biodiversity ‘hotspots’ around the world. Most countries with parks and protected areas now have some kind of marketing strategy to attract ecotourists. Increasing numbers of universities in the USA and abroad now offer courses and degree programmes in ecotourism. The United Nations declared 2002 the ‘International Year of Ecotourism’ and marked it as a time to take collective stock of the lessons learned. At the Ecotourism World Summit in Quebec, Canada, thousands of delegates from over a hundred nations gathered to assess the pros and cons of ecotourism for peoples and ecosystems around the world